2019
DOI: 10.14202/vetworld.2019.211-217
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of proteolysis of high protein silage from Moringa and Indigofera leaves by addition of tannin extract

Abstract: Aim: The objective of this experiment was to evaluate the effect of the addition of tannin extract to Moringa and Indigofera leaf silages on their chemical composition, silage quality characteristics, and in vitro rumen fermentation parameters and digestibility. Materials and Methods: Moringa and Indigofera leaves were cut (3 cm length) and added with either 0, 2, or 4% chestnut tannin in three replicates. The leaves were then inserted into lab-scale silos (1 L capacity) and kept for 30 days. Silage samples we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 44 publications
2
14
0
Order By: Relevance
“…Furthermore, the addition of tannins did not alter the NDF and ADF contents, which has also been reported by other studies [28,29]. Such unchanged NDF and ADF contents in silage indicate the lower affinity of tannins on fiber components compared to protein [9].…”
Section: Nutrient Composition and Fermentation Characteristics Of Ensiled Ssbsupporting
confidence: 87%
See 1 more Smart Citation
“…Furthermore, the addition of tannins did not alter the NDF and ADF contents, which has also been reported by other studies [28,29]. Such unchanged NDF and ADF contents in silage indicate the lower affinity of tannins on fiber components compared to protein [9].…”
Section: Nutrient Composition and Fermentation Characteristics Of Ensiled Ssbsupporting
confidence: 87%
“…Tannins are a naturally occurring polyphenol that have the ability to interact with other molecules, particularly protein, due to the presence of hydroxyl groups in their structure [8]. A previous study reported that tannin extract from chestnuts could inhibit proteolysis in Moringa and Indigofera leaf silages, as indicated by the lower ammonia (NH 3 ) concentration [9]. Furthermore, a meta-analysis revealed that higher tannin levels in the ensiled material resulted in lower NH 3 and butyrate concentrations [10], indicating its potential application as a silage additive.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the best pH, total VFA, and NH 3 values were achieved using the rations with I. zollingeriana (IZ I and IZ II). In this study, the pH range (6.9 to 7) of the rumen fluid on the basis of the I. zollingeriana (freshly cut) ration was at an ideal level compared to the pH ranges reported by the previous studies that used feed preservation technology in the form of Indigofera silage and pellet [36,37]. The NH 3 production differed significantly (p<0.05) among groups and was highest in IZ I.…”
Section: Discussionmentioning
confidence: 52%
“…This tannin can only release its bonds with feed ingredients by enzymes in the small intestine and low pH levels, while in the rumen, tannins are problematic in the rumen bacterial break and normal rumen pH (Jamarun and Zain 2013). Tannin addition increased neutral detergent insoluble crude protein (NDICP) and acid detergent insoluble CP (ADICP) (Jayanegara et al 2019). However, the levels should not be excessive because if excessive phytochemicals can hurt livestock productivity.…”
Section: Phytochemical Contentsmentioning
confidence: 99%